THE EFFECT OF LEARNING PROBLEM POSING ON THE ABILITY OF MATHEMATICS CONCEPTS UNDERSTANDING OF STUDENTS IN CLASS XI IPA OF SMA AL-FALAH - Rifka Agustianti; Nurwirhanuddin Nurwirhanuddin; Ruben Sonda; Maria Letisia Lipa Tupen; A. Rasul (Daya Matematis: Jurnal Inovasi Pendidikan Matematika, 2023)
The aims of this study were (1) to find out the differences in the ability to understand mathematical concepts between students in classes who received problem posing learning and students in classes who received conventional learning. (2) Knowing the differences in the ability to understand mathematical concepts between students in the high, medium and low groups in terms of the level of mastery of mathematics. (3) Knowing the interaction between the learning model and the level of mastery of mathematics in the ability to understand mathematical concepts. This research is an experimental research with research units determined based on learning groups and the level of students' mastery of mathematics. Learning groups are divided into two, namely problem posing learning and conventional learning. While the level of students' mastery of mathematics is divided into high, medium and low groups. The population in this study were all students of class XI IPA at SMAN Al-Falah. The research sample was class XI IPA 1 as the experimental class and class XI IPA 2 as the control class. Based on the results of data analysis, the following conclusions are obtained: (1) There are differences in the ability to understand mathematical concepts between students who receive problem posing learning and students who receive conventional learning. (2) There are differences in the ability to understand mathematical concepts between students in the high and medium and high and low groups. But there is no difference in the ability to understand mathematical concepts between students in the medium and low groups.